2007
DOI: 10.1007/s00244-007-9039-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Perfluorobutane Sulfonate (PFBS) on the Mallard and Northern Bobwhite Quail

Abstract: Perfluorobutane sulfonate (PFBS) can be a final degradation product of perfluorobutane sulfonyl fluoride (PBSF)-based chemicals. Surfactants based on this chemistry are potential replacements for perfluorooctane sulfonate (PFOS)-related products and have many potential applications in industrial and commercial processes and applications. To evaluate the potential hazard that PFBS may pose to avian species, acute dietary studies with juvenile mallards and northern bobwhite quail, as well as a quail dietary chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 24 publications
(26 reference statements)
2
43
0
Order By: Relevance
“…The results showed that around 100% of the PFOS in the egg was distributed in egg yolk and PFOS was not detected in egg white (<0.08 ng/g, w/w). Our results were consistent with another study which reported that approximately 98% of the PFOS measured in eggs was found in the yolk, whereas less than 1% was measured in the albumen and egg membrane [31] . The results of these two studies suggest that most of the PFOS transferred to bird eggs partitions to the yolk, but more studies on other species are needed to confirm this finding.…”
Section: Dietary Survey and Risk Assessmentsupporting
confidence: 95%
See 1 more Smart Citation
“…The results showed that around 100% of the PFOS in the egg was distributed in egg yolk and PFOS was not detected in egg white (<0.08 ng/g, w/w). Our results were consistent with another study which reported that approximately 98% of the PFOS measured in eggs was found in the yolk, whereas less than 1% was measured in the albumen and egg membrane [31] . The results of these two studies suggest that most of the PFOS transferred to bird eggs partitions to the yolk, but more studies on other species are needed to confirm this finding.…”
Section: Dietary Survey and Risk Assessmentsupporting
confidence: 95%
“…Consumption of tainted foodstuffs might be one of the possible sources of contamination. Besides, a recent study reported that food-packaging processes might contribute PFC contamination to food [31] . Conceivably, surfactant in the packaging of chicken feed might contaminate chicken feed with PFCs, and the consumption of contaminated foodstuffs may have resulted in the relatively high PFOS concentrations that were detected in the chicken eggs.…”
Section: Special Topics Articlesmentioning
confidence: 99%
“…PFAS are ubiquitous in river water, oceans, sediment, soil, and tissues of wildlife and humans (Ahrens et al, 2010a;Higgins et al, 2005;Wang et al, 2013;Giesy and Kannan, 2001;Bao et al, 2010a;Kannan et al, 2001Kannan et al, , 2002a. They are potentially harmful to fresh water and marine mammals (Ishibashi et al, 2008) and have potential adverse effects in wildlife species (Hoff et al, 2005;Fair et al, 2012;Beach et al, 2005;Newsted et al, 2005Newsted et al, , 2008Giesy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results however, demonstrated significantly altered heart rates in the embryos as well as malformations of their heads after exposure to PFBS (Hagenaars et al, 2011b). In juvenile mallards and northern bobwhite quail, PFBS was found to affect the body weight gains of quail exposed to 5,620 or 10,000 mg PFBS/kg feed, which were statistically less than that of unexposed controls (Newsted et al, 2008).…”
Section: Perfluoroalkyl Sulfonates (Pfsas)mentioning
confidence: 81%